Diagnostic value of serum procalcitonin, neopterin, and gamma interferon in neonatal calves with septicemic colibacillosis. (March 2016) - Ercan, Nazli; Tuzcu, Nevin; Başbug, Onur; Tuzcu, Mehmet; Alim, Ahmet
The objective of our study was to compare the serum concentrations of procalcitonin (PCT), neopterin, tumor necrosis factor alpha (TNF-α), prostaglandin E2, malondialdehyde, interleukin 8, and gamma interferon (IFN-γ) in neonatal calves with septicemic colibacillosis ( n = 15) with healthy controls ( n = 15). Septicemic colibacillosis was diagnosed based on clinical signs and the isolation of Escherichia coli from heparinized blood in clinically suspected cases. PCT, neopterin, TNF-α ( p < 0.05), and IFN-γ concentrations in calves with septicemic colibacillosis were significantly higher than in the healthy controls ( p < 0.01). Serum PCT concentrations were 4 times higher in the calves with septicemic colibacillosis than in the healthy calves, suggesting that PCT could be a useful marker of septicemic colibacillosis in neonatal calves.